Treatment with organic manure inoculated with a biocontrol agent induces soil bacterial communities to inhibit tomato Fusarium wilt disease - Tang, Tongtong; Sun, Xing; Liu, Qin; Dong, Yuanhua; Zha, Mingfang (Frontiers in Microbiology, 2023)
Organic manure, plant growth-promoting microorganisms, and biocontrol agents are widely used to sustainably control soil-borne diseases. However, how and whether organic manure inoculated with biocontrol agents alters soil microbiota and reduces disease severity is poorly understood. Here, we examined changes to the soil microbial community, soil properties, and incidence of Fusarium wilt disease in response to several fertilization regimes. Specifically, we studied the effects of inorganic chemical fertilization (CF), organic manure fertilization (OF), and Erythrobacter sp. YH-07-inoculated organic manure fertilization (BF) on the incidence of Fusarium wilt in tomato across three seasons. BF-treated soils showed increased microbial abundance, richness, and diversity compared to other treatments, and this trend was stable across seasons. BF-treated soils also exhibited a significantly altered microbial community composition, including increased abundances of Bacillus, Altererythrobacter, Cryptococcus, and Saprospiraceae, and decreased abundances of Chryseolinea and Fusarium. Importantly, BF treatment significantly suppressed the incidence of Fusarium wilt in tomato, likely due to direct suppression by Erythrobacter sp. YH-07 and indirect suppression through changes to the microbial community composition and soil properties. Taken together, these results suggest that Erythrobacter sp. YH-07-inoculated organic manure is a stable and sustainable soil amendment for the suppression of Fusarium wilt diseases.